1935
DOI: 10.1113/expphysiol.1935.sp000682
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Lactic Acid Into and Out of the Voluntary Muscles of the Frog

Abstract: 1. Observations on the diffusion of d‐lactate in and out of resting frog muscle during immersion in a Ringer's solution containing sodium d‐lactate show that only about one‐third of the muscle water appears to be involved in the diffusion process, the rest appearing to be shut off by membranes impermeable to lactate. These two portions of muscle have been termed “interspaces” and “cells” respectively. 2. In the fatigued muscle, the “interspaces” tend to disappear presumably due to a swelling of the “cells” on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1935
1935
1975
1975

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It is of interest to examine the early work of Ghaffar (1935) who equilibrated frog gastrocnemii at 00 C in Ringer, in which 0-50 mM-NaCl had been replaced by Na L-lactate. The muscle lactate concentration linearly related to that in the bath, with a ratio of distribution between muscle water and medium of about 0 3.…”
Section: Resultsmentioning
confidence: 99%
“…It is of interest to examine the early work of Ghaffar (1935) who equilibrated frog gastrocnemii at 00 C in Ringer, in which 0-50 mM-NaCl had been replaced by Na L-lactate. The muscle lactate concentration linearly related to that in the bath, with a ratio of distribution between muscle water and medium of about 0 3.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that in the case of the diffusion of some of these substances, for example, phosphate and lactate, only a fraction of the muscle water seems to be involved in the diffusion process, the rest appearing to be shut off by membranes impermeable to these ions [M. G. Eggleton, 1933;Ghaffar, 1935].…”
mentioning
confidence: 99%
“…It has also been shown that in the case of the diffusion of some of these substances, for example, phosphate and lactate, only a fraction of the muscle water seems to be involved in the diffusion process, the rest appearing to be shut off by membranes impermeable to these ions [M. G. Eggleton, 1933;Ghaffar, 1935].This communication gives the results of certain observations in the diffusion of iodide (an ion not normally present in the animal body), through the frog muscle, and an attempt is made to correlate the low coefficient of diffusion in the case of living muscle to the inability of iodide to diffuse through a fraction of the muscle water. …”
mentioning
confidence: 99%